The prevalence of CCR5‐Δ32 mutation in a cohort of Saudi stem cell donors. (28th August 2017) - Alarifi, M.; Al‐Amro, F.; Alalwan, A.; Al‐Turki, A.; Fakhoury, H.; Atallah, N.; Al‐Muallimi, M.; Al‐Balwi, M.; Alzahrani, M.; Alaskar, A.; Hajeer, A.; Jawdat, D.
Abstract : CCR5 is a chemokine receptor that was found to be used by HIV as a co‐receptor for entering target cells. A 32 bp deletion was described in certain people that rendered CCR5 non‐functional. The mutant allele CCR5‐Δ32 has been shown to prevent HIV infection. In addition, stem cell transplantation with the CCR5‐Δ32 homozygous genotype can lead to clearance of HIV infection. In this study, our aim was to investigate the frequency of CCR5‐Δ32 mutation in a cohort of stem cell donors from cord blood bank and stem cell donor registry. A total of 3025 samples were collected from healthy stem cell donors (2625) and from cord blood units (400). DNA was extracted and the CCR5 gene was amplified by polymerase chain reaction (PCR) in a light cycler system using SYBR Green dye. The mutated gene was further confirmed by direct gene sequencing. We found 38 heterozygous for CCR5‐Δ32 and one homozygous CCR5 mutation (Δ32/Δ32) out of the 3025 tested individuals. We conclude that the protective CCR5‐Δ32 allele appears to be rarely present in Saudi Arabia.